PROSPEK PEMANFAATAN TANAH WAKAF DI ACEH: SUATU ANALISIS UNTUK SEKTOR PENDIDIKAN - azharsyah, azharsyah (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2015)
In Islamic law known as waqf property are ibdal and istibdal. Three schools namely, Shafii, Maliki, Jafari impressed and very cautious in allowing the sale and replacement of goods endowments. Basically, the community hold the principle that the waqf land should only be attempted or managed by the trust Wakif, in general, because the donated land is handed over to the mosque, then using or utilization should also be utilized for mosques. Perwakafan circumstances contained in Aceh Besar district, especially in the two sub objects once the research potential to be developed primarily to finance the education sector.